Effectiveness Wound Care Using Modern Dressing Method To Diabetic Wound Healing Process Of Patient With Diabetes Mellitus - Windu Santoso; joyo purnomo (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
Diabetes mellitus causes a lot of various complaints and complications. One of the most serious and most common complications is diabetic ulcers. Prevention of diabetic ulcer complications can be done with comprehensive wound care. The Appropriate wound care management can prevent amputation. One of a method of wound care that can accelerate the wound healing process is modern dressing wounds. This researched aim to analyze the effectiveness of wound care using modern dressing method to the diabetes mellitus patients. The research design was pre-experimental one group pre-test post-test with 15 samples.Ã‚ The data analyzed using Paired T-test. The result of data analysis using Paired T-test with significance level of 5% obtained ÃÂ = 0,000 and the average value of wound development before and after wound treatment using modern dressing method has decrease from 39,67toÃ‚ 29,93 because wound care with modern dressing method make environment of wound is moist so that capitalization and granulation process growth up be faster. So it can be concluded that there is an effect of wound care using modern dressing method to the wound healing process with diabetes mellitus.